Effect of Various Inoculum Levels of Multidrug-Resistant Salmonella enterica Serovar Heidelberg (2011 Ground Turkey Outbreak Isolate) on Cecal Colonization, Dissemination to Internal Organs, and Deposition in Skeletal Muscles of Commercial Turkeys after Experimental Oral Challenge - Nair, Divek V. T.; Vazhakkattu Thomas, Jijo; Noll, Sally; Porter, Robert; Kollanoor Johny, Anup (Frontiers in Microbiology, 2018)
Salmonella enterica serovar Heidelberg (S. Heidelberg) is a major foodborne pathogen colonizing poultry. The pathogen is associated with a significant number of foodborne outbreaks through contaminated poultry meat, including turkeys. Recently, multidrug-resistant (MDR) strains of S. Heidelberg have emerged as a threat to human public health in the U.S. The objective of this study was to determine the cecal colonization, dissemination to internal organs, and the potential for skeletal muscle deposition of an MDR S. Heidelberg isolate from the 2011 ground turkey outbreak in the U.S. after the experimental oral challenge of poults (young turkeys) and adult turkey hens. In the poult study, two separate experiments using day-old, straight-run, commercial hybrid converter poults were randomly assigned to five challenge groups (0, 10^2, 10^4, 10^6, 10^8 CFU groups; 12 poults/group; N=60/experiment) and a week after, treatment groups were challenged separately with 0-, 2-, 4-, 6- and 8- log10 CFU of S. Heidelberg orally. After 14 days post-challenge, the poults were euthanized, and samples were collected to determine MDR S. Heidelberg colonization in the cecum, dissemination to liver and spleen, and deposition in the thigh, drumstick, and breast muscles. A similar experimental design was followed for the adult turkey hens. In two separate experiments, 11-week-old commercial hybrid converter turkey hens (4 hens/group; N=20/experiment) were challenged with MDR S. Heidelberg and on day 16 post-challenge, birds were euthanized and samples were collected to determine Salmonella populations in the samples. The results indicated that, in turkey poults, the recovery of MDR S. Heidelberg was highest in the cecum followed by spleen, liver, thigh, drumstick, and breast. All tested inoculum levels resulted in more than 3.5 log10 CFU/g colonization in the poult cecum. The cecal colonization, dissemination to internal organs, and tissue deposition of MDR S. Heidelberg were high in poults. The pathogen recovery from the cecum of adult turkey hens ranged from 37.5 to 62.5% in the challenge groups. The results signify the importance of controlling MDR S. Heidelberg in turkeys at the farm level to improve the safety of turkey products.